2. The Second World War and Its Aftermath - Committee, Editorial (Historein, 2013)
Giorgos Antoniou, review of A war without end: the 1940s in political discourse, 1950-1967, by Eleni Paschaloudi. Kateřina Králová and Konstantinos Tsivos, review of Children of the Greek Civil War: Refugees and the Politics of Memory, by Loring M. Danforth and Riki van Boeschoten. Christina Alexopoulos, review of Staying temporarily: Greek political refugees in the People's Republic of Bulgaria, 1948-1982, by Katerina Tsekou. Eugenia Bournova, review of Famine and death in occupied Greece, 1941-1944, by Violetta Hionidou. Iordanis Psimmenos, review of Construction workers: The people who built Athens, 1950-1967, by Dimitra Lambropoulou.